Strategies Applied in Translating InformationTechnology Terms in Manual Books: Iphone 12 Pro and Samsung S20 FE - Eksanti Dwi Pratiwi; Ahmad Juma' Khatib (Bina Nusantara University, 2021)
The research focused on the translation of technological terms in iPhone 12 Pro and Samsung S20 FE manual books from English into Indonesian. The research applied a descriptive qualitative approach. The Chesterman’s translation strategies were used to find out how Information Technology (IT) terms were translated from English into Indonesian. The research finds that four translation strategies are used to translate the manual book of the iPhone 12 Pro and Samsung S20 FE from English into Indonesian. From the total of 60 data, the four strategies are loan (35 data), calque (11 data), unit shift (13 data), and the least used strategies are information change (1 data). It can be concluded that the most frequently used strategies are loan (35 data), while the least used strategies are information change (1 data).